Conceptualization and frequency of sampling (mal)practices in L2 inferential quantitative research: Towards a potential QRP? - Vitta, Joseph P.; Hahn, Aaron; Canning, Derek; Isbell, Daniel R.; Al-Hoorie, Ali H.; Nicklin, Christopher (Journal of Second Language Studies, 2025)
Poor sampling practices can constitute a questionable research practice when conducting L2 inferential quantitative research. The current study, a methodological synthesis (N = 433 Scopus/Web of Science (WoS) reports: cluster random sampling) of sampling practices, revealed that L2 inferential quantitative researchers rarely employed randomized and/or effect size-driven sampling processes with only eight (1.8%) and ten (2.3%) of the reports being respectively satisfactory. Furthermore, just 33.9% of the reports featured multisite (convenience) samples. In models assessing what predicted multisite sampling, whether the report was ISLA-focused (r = −.33, p <.001) or single-authored (r = −.15, p <.001) incurred moderate and weak negative associations. Citation analysis metric values and the Scopus/WoS contrast had no associations. The findings of this study suggest the field's sampling practices have room to improve and guidance for future improvement is offered.